Examining the Sources of Violent Victimization Among Jail Inmates. (November 2018) - Ellison, Jared M.; Steiner, Benjamin; Wright, Emily M.
This study involves an examination of the individual- and jail-level predictors of violent victimization during short-term incarceration using data from the most recent Survey of Inmates in Local Jails and the corresponding National Jail Census. Findings suggest that individuals whose attributes make them appear more vulnerable or whose attributes antagonize others have a greater risk of violent victimization in jail. In addition, the findings suggest that jails with more stagnant inmate populations and older jails may have higher levels of violent victimization. Overall, the study results add validity to the opportunity framework as a general explanation for victimization risk regardless of the setting in which individuals are placed.